2021
DOI: 10.17818/emip/2021/2.13
|View full text |Cite
|
Sign up to set email alerts
|

PREDICTING NPLs FOR CROATIA WITH MACROECONOMIC VARIABLES

Abstract: This paper aims to examine some of the macroeconomic drivers of nonperforming loans (NPL) in Croatia. Unemployment rate, industrial production index, construction works volume and the number of tourist arrivals were evaluated as the drivers on a quarterly data sample from 2008q4 to 2020q4. Following quantile regression approach, unemployment rates and construction works volume appeared as significant drivers of NPL in Croatia. Furthermore, empirical findings from this paper suggest asymmetric effects on NPL fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Nedavna primjena kvantilnog regresijskog pristupa može se naći u Bošnjak et al (2020) ili Bošnjak et al (2021). Općenito, jednadžba je procijenjena primjenom kvantilnog regresijskog pristupa -kako bi se ilustrirali učinci kvantile zavisne varijable.…”
Section: Research Data and Methodologyunclassified
See 1 more Smart Citation
“…Nedavna primjena kvantilnog regresijskog pristupa može se naći u Bošnjak et al (2020) ili Bošnjak et al (2021). Općenito, jednadžba je procijenjena primjenom kvantilnog regresijskog pristupa -kako bi se ilustrirali učinci kvantile zavisne varijable.…”
Section: Research Data and Methodologyunclassified
“…Recent application of quantile regression approach can be found in Bošnjak et al (2020) or Bošnjak et al (2021) among others. In general, equation was estimated by using quantile regression approach -to illustrate effects across quantile of dependent variable.…”
Section: Research Data and Methodologymentioning
confidence: 99%
“…Many studies have attempted to explore the effects of macroeconomic determinants on non-performing loans which had derived several variables such as gross domestic product rate, inflation rate, interest rate, exchange rate, unemployment rate, etc. Notable among them is the study conducted by Bošnjak et al (2021). They examine the impact of some macroeconomic determinants on non-performing loans in Croatia and revealed that the unemployment rate and construction work volume have an impact on the NPL levels.…”
Section: Related Researchesmentioning
confidence: 99%